2011
DOI: 10.1097/nrl.0b013e31823968fc
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Dopamine Agonists

Abstract: Parkinson disease is a progressive neurodegenerative disease that affects, among other neurotransmitter systems, the nigrostriatal dopaminergic projection. Palliative treatment with levodopa and/or dopamine agonists improves motor symptoms even though patients continue to get clinically worse by the neurodegenerative process that continues to act as the major factor of physiological aging. Studies (in vitro and in vivo) with experimental models have shown that dopamine agonists have neuroprotective effects, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…The ELLDOPA trial in 2004 [91] refuted these findings, and the American Academy of Neurology (AAN) guidelines in 2006 used this evidence to state that L-dopa did not accelerate disease progression [92]. There was vigorous debate in the field at this time on the benefits of commencing therapy with DA agonists to delay onset of L-dopa-induced dyskinesia (LID) and other potential benefits of reduced development of LID we anticipated might have altered prescribing but this was only evident in marginal trends [93, 94]. Recently, the LEAP study revealed that L-dopa has no disease-modifying effects [95]; however, the high reliance on L-dopa could be explained by its higher efficacy and better safety profile than other PD medications [96, 97].…”
Section: Discussionmentioning
confidence: 99%
“…The ELLDOPA trial in 2004 [91] refuted these findings, and the American Academy of Neurology (AAN) guidelines in 2006 used this evidence to state that L-dopa did not accelerate disease progression [92]. There was vigorous debate in the field at this time on the benefits of commencing therapy with DA agonists to delay onset of L-dopa-induced dyskinesia (LID) and other potential benefits of reduced development of LID we anticipated might have altered prescribing but this was only evident in marginal trends [93, 94]. Recently, the LEAP study revealed that L-dopa has no disease-modifying effects [95]; however, the high reliance on L-dopa could be explained by its higher efficacy and better safety profile than other PD medications [96, 97].…”
Section: Discussionmentioning
confidence: 99%
“…Continued disagreement regarding the toxicity of levodopa likely contributed to the observed delay in response. The notion that DAs are less toxic (rather than simply less potent) continues to have a strong footing in the scientific literature and lay press [ 31 , 32 ]. Notwithstanding any disagreement, recent evidence reaffirms the AAN’s finding that levodopa is not toxic [ 10 , 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While L-dopa is still the pharmacological gold standard for PD, among other symptomatic treatments for motor symptoms of PD, DA receptor agonists had been found to be promising, although their use in the clinic is still nondefinitive. Among neuroprotective strategies to limit the PD progression, D2 DA receptor agonists are often a part of pharmacological therapy for early PD 24 26 and could protect neurons of both the nucleus striatum and the substantia nigra by a variety of actions including the modulation of mitochondrial function. Thus, neuroprotection of cortico- and nigrostriatal circuits is a direct consequence of the restorative dopaminergic strategies.…”
Section: Introductionmentioning
confidence: 99%